Millimeter-wave TE01–TE11–HE11 mode converter using overmoded circular waveguide. Issue 14 (22nd September 2018) - Patel, Amit; Goswami, Riddhi; Vala, Alpesh; Mahant, Keyur; Mewada, Hiren; Bhatt, Pujita; Sathyanarayan, K.; Kulkarni, S. V.
Abstract: The paper presents overmoded circular waveguide mode converters (TE01 into HE11 with TE11 as an intermediate mode) used in a 42 ± 0.2 GHz, 200 kW gyrotron transmission line system for plasma heating in electron cyclotron resonance heating application. To convert mode from TE01 to TE11, we have used wriggle converter method with a deformation in the converter axis and for TE11 to HE11 mode converter the depth of corrugation decreases gradually from to . Both the converters are optimized in terms of design parameters using mode field matching technique. The TE01 to TE11 mode converter showed a conversion efficiency of 95% (predicted 99%) for a length of 1205 mm, while TE11 to HE11 mode converter gave conversion efficiency of 99% (predicted 99.98%) for a diameter of 32 mm. Cross-polarization isolation of 31.7 dB is obtained in TE11 to HE11 mode converter. Convergence of the theoretical values and the simulated results indicates that the converters meet the system requirements.